2009
DOI: 10.1123/mcj.13.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Postural Coordination on Rigid and Non-Rigid Surfaces

Abstract: When two standing people converse with each other there is an increase in their shared postural activity, relative to conversation with different partners. We asked pairs of participants to converse with each other or with experimental confederates while standing on rigid and nonrigid surfaces. On the rigid surface, shared postural activity was greater when participants conversed with each other than when they conversed with confederates. In addition, the strength of interpersonal coupling increased across tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
6
23
0
Order By: Relevance
“…To permit comparison of our results with these literatures we used dependent measures that were used in previous studies. To evaluate the magnitude of postural activity we used the positional variability of the head and waist in the anterior-posterior axis (Stoffregen, Giveans, et al, 2009;. Positional variability was operationally defined as the standard deviation of head and waist position over the duration of each trial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To permit comparison of our results with these literatures we used dependent measures that were used in previous studies. To evaluate the magnitude of postural activity we used the positional variability of the head and waist in the anterior-posterior axis (Stoffregen, Giveans, et al, 2009;. Positional variability was operationally defined as the standard deviation of head and waist position over the duration of each trial.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research with individuals (Stoffregen et al, 2000;Stoffregen et al, 1999), we predicted that target distance would influence the positional variability of the head and waist of individual participants such that positional variability should be greater when targets were farther away than when targets were closer. Following Shockley et al (2003) and Stoffregen, Giveans, et al (2009), we preDownloaded by [Uniwersytet Warszawski] at 00:22 27 November 2014 dicted that task partner would influence parameters of CRQ for dyads such that recurrence measures would be lower when participants were talking to confederates than when talking to each other. Finally, based on the findings of Stoffregen, Giveans, et al (2009) we predicted that task partner would also influence the positional variability of individuals such that when talking to one's task partner, postural sway variability would be lower than when talking to an experimenter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…That phenomenon may reflect a relation between speech production and body movement termed self-synchrony (Condon & Ogston, 1967;Condon, 1988). Recently, it has also been found that simply engaging in a conversation with another person promotes coordination of postural sway patterns (Shockley et al, 2003;Stoffregen, Giveans, Villard, & Shockley, 2013;Stoffregen, Giveans, Villard, Yank, & Shockley, 2009), an outcome consistent with previous well-known findings of interpersonal coordination (e.g., Condon & Ogston, 1967;LaFrance, 1979;LaFrance, 1985;Newtson, Hairfield, Bloomingdale, & Cutino, 1987). However, the functional role of interpersonal coordination with respect to effective communication and other measures of mutual cognitive alignment, such as joint attention (Sebanz, Bekkering, & Knoblich, 2006), has yet to be clearly identified.…”
mentioning
confidence: 99%